2008
DOI: 10.22201/icat.16656423.2008.6.02.516
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the powder obtained from wasted tires reduced by pyrolysis and thermal shock process

Abstract: This paper reports on the physicochemical characterization of solid powder obtained directly from wasted tires through pyrolysis and thermal shock process. Two different processes to reduce wasted tires were performed in order to acquire the residuals in powder to be characterized and compared.During this research, three phases were observed when pyrolysis was applied to rubber: the first one a solid black phase formed by organic and inorganic compounds such as zinc oxide (ZnO) and zinc sulphur (ZnS); secondly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…In the temperature range between 80 and 350 ∘ C all the minor constituents are lost, as they are normally volatile materials such as low molecular weight oligomers, plasticizers, emulsifications, oils and waxes, and antioxidants. The degradation process of major constituents or their combinations occurs between 340 and 550 ∘ C. It was previously indicated that the maximum mass loss of styrene-butadiene rubber occurs at 350 and 500 ∘ C, maximum degradation of natural rubber at 373 ∘ C, and for butadiene rubber at 372 and 460 ∘ C. Finally, in the last degradation phase, above 500 ∘ C only about 34% of the original weight of the sample is left, corresponding to decomposition products mainly containing Zn and carbon atoms such as oxidized no-volatile materials, carbon black, and graphite [18,19]. However, in the case of rubber combinations like those used in tires, it is observed that the mass loss for each peak in the thermogram curves is dependent on the composition of the mixture.…”
Section: Solid Powder Residue Characterization According To Ftir (mentioning
confidence: 99%
“…In the temperature range between 80 and 350 ∘ C all the minor constituents are lost, as they are normally volatile materials such as low molecular weight oligomers, plasticizers, emulsifications, oils and waxes, and antioxidants. The degradation process of major constituents or their combinations occurs between 340 and 550 ∘ C. It was previously indicated that the maximum mass loss of styrene-butadiene rubber occurs at 350 and 500 ∘ C, maximum degradation of natural rubber at 373 ∘ C, and for butadiene rubber at 372 and 460 ∘ C. Finally, in the last degradation phase, above 500 ∘ C only about 34% of the original weight of the sample is left, corresponding to decomposition products mainly containing Zn and carbon atoms such as oxidized no-volatile materials, carbon black, and graphite [18,19]. However, in the case of rubber combinations like those used in tires, it is observed that the mass loss for each peak in the thermogram curves is dependent on the composition of the mixture.…”
Section: Solid Powder Residue Characterization According To Ftir (mentioning
confidence: 99%
“…Moreover, it is necessary to have in mind how waste tires can be converted into a valuable resource [1]. Recycling of such materials has been carried out by different processes, including (a) landfilling, which diminishes in some countries due to new laws that forbid any new landfill; (b) producing powder richer in carbon compounds by pyrolysis process, which consist in the decomposition of the organic materials by heating at 400 ∘ C in absence of oxygen; pyrolysis sometimes is not economically viable due to low quality final products; nevertheless, it is possible to obtain three different phases through all processes, (1): solid black phase composed by ZnO and ZnS; (2): gaseous phase containing aromatic compounds; and (3): liquid phase with heavy and light oils [2][3][4]; (c) using as fuel in cement kilns, whose cost is lower than raw tire materials, which is an example of downcycling process [4]; (d) recycling by shredding process, where waste tires particles require having certain size for specific applications, varying from 0.15 mm to 2 International Journal of Polymer Science 19 mm; after shredding an electromagnetic process is applied for separation of rubber particles and steel fibers, for reusing them in several applications, for making rubber products such as floor mats, carpet padding, and plastic products, and as a substitute of fine aggregate in concrete [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The usage of waste tires as alternative fuel in cement furnaces is generalized across the US and Europe [5]. However, these practices result in the generation of organic and inorganic compounds such as zinc oxide (ZnO) and zinc sulfide (ZnS), in hydrocarbon gas, aromatic volatile compounds, liquids formed by heavy and light oils, and all these byproducts which are highly polluting [6].…”
Section: Introductionmentioning
confidence: 99%